A cellular deficiency of gangliosides causes hypersensitivity to Clostridium perfringens phospholipase C - Flores Díaz, Marietta (2005)
Clostridium perfringens phospholipase C (Cp-PLC), also called alpha-toxin, is the major virulence factor in the pathogenesis of gas gangrene. Previously, a cellular UDP-Glc deficiency was related with a hypersensitivity to the cytotoxic effect of Cp-PLC. Because UDP-Glc is required in the synthesis of proteoglycans, N-linked glycoproteins, and glycosphingolipids, the role of these gly-coconjugates in the cellular sensitivity to Cp-PLC was studied. The cellular sensitivity to Cp-PLC was significantly enhanced by glycosphingolipid synthesis inhibitors, and a mutant cell line deficient in gangliosides was found to be hypersensitive to Cp-PLC. Gangliosides protected hypersensitive cells from the cytotoxic effect of Cp-PLC and prevented its membrane-disrupting effect on artificial membranes. Removal of sialic acids by C. perfringens sialidase increases the sensitivity of cultured cells to Cp-PLC and intramuscular co-injection of C. perfringens sialidase, and Cp-PLC in mice potentiates the myotoxic effect of the latter. This work demonstrated that a reduction in gangliosides renders cells more susceptible to the membrane damage caused by Cp-PLC and revealed a previously unrecognized synergism between Cp-PLC and C. perfringens sialidase, providing new insights toward understanding the pathogenesis of clostridial myonecrosis.